Nutritional Support for Chronic Disease - Gropper, Sareen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Diet contributes to the development of many chronic conditions including obesity, cardiovascular disease, hypertension, stroke, type 2 diabetes, metabolic syndrome, some cancers, non-alcoholic fatty liver disease, and potentially some neurological diseases. This reprint addresses associations between diet (and specific nutrients including vitamin D) and various chronic diseases including obesity, cardiovascular disease, hypertension, stroke, diabetes, metabolic syndrome, non-alcoholic fatty liver disease, neurological conditions, and age-related macular degeneration. More specifically, the impacts of plant-based diets, dairy products, and ketogenic diets are explored in relation to chronic disease risk as well as some benefits of the consumption of oral nutritional supplements in the prevention of malnutrition and sarcopenia and in the treatment of wounds in individuals with diabetes. Additional topics that are covered include some roles of the fatty acid arachidonic acid in the body and the impact of cellular mitochondrial dysfunction on the progression of age-related macular degeneration. The effectiveness of a variety of nutraceuticals is covered as a means for the prevention or treatment of age-related macular degeneration. Lastly, the use of olive oil in reducing gut permeability in those with pre-diabetes is addressed, as well as the complex relationships of diet/food and of disease (metabolic syndrome) with the gut microbiota.